Estudo limnológico de um trecho do médio rio Madeira (região de Porto Velho - RO), com ênfase na comunidade Zooplanctônica - Arantes Junior, João Durval (2011)
Madeira River is the fourth major river of the planet considering its discharge, only behind the Amazonas, Congo and Orinoco rivers. It is the main affluent contributing with half of the suspended solids transported by the Amazon River. In the present work a limnological research was carried out in a 300 Km stretch of Middle Madeira River. Two different approaches were adopted in order to characterize physically and chemically the system: A real time monitoring of physical and chemical variables at short time intervals and trimestrally punctual surveys. Seven field expeditions were carried out corresponding to different hydrological periods: decreasing water level, low water, rising water level and high waters. Eight sampling stations were distributed along the 300 km of River Madeira stretch for measurements of physical and chemical variables, plus water and plankton samples collection. Some variables were measured in situ by the Yellowsprings multiparameter probe and water was taken for laboratory suspended matter, nutrient and ion cocentration measurements. In the real time monitoring the measurements were taken each 30 minutes along 423 days in the period between 23/01/2010 and 22/03/2011. The results obtained evidenced the strong influence of the hydrological cycle on the water turbidity, electrical conductivity, dissolved oxygen concentration and pH. Short time pulses starting with abrupt changes in the water level and discharge of River Madeira greatly influenced water turbidity and electrical conductivity. The zooplankton community was composed by 101 taxa, being Rotifera the group of highest species richness (45 species). Copepoda was a group with noticeably high richness of species, being represented by fifteen species, among which some Amazon endemic taxa. Total diversity is moderate compared to other fluvial systems in Brazil. Protozoa was the group that contributed most to the zooplankton biomass particularly in the periods of decreasing water and low water levels of the year 2010. Mean density of zooplankton was 9,714 ind. m-3 and mean biomass was relatively low with a mean value of 14.22 x 103 μg.m-3. The zooplankton community is probably limited by the low primary productivity of this white water river and primarily responds to the wide fluctuaions of the main driving forces of the system, both the seasonal and interannual changes in the river water level.